2023
DOI: 10.1155/2023/1008075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 Huff and Puff Rounds on Crude Oil Properties

Abstract: In view of the deterioration of oil well liquid supply capacity and oil increase effect after multiple rounds of carbon dioxide (CO2) huff and puff, according to the actual conditions of the Ng12 reservoir in the XA oilfield, an indoor physical simulation experimental model was established. The experimental parameters were determined, five rounds of CO2 huff and puff experiments were carried out, and the crude oil produced in the water flooding stage and different rounds of CO2 huff and puff were collected. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For the experimental study of indoor CO 2 huff and puff, some scholars compared the mining effects under N 2 and CO 2 injection by carrying out shale oil huff and puff experiments with N 2 and CO 2 injection, and verified the huge potential of CO 2 huff and puff in improving shale oil recovery. Also, by studying the effects of permeability, fracture, injection pressure, miscible conditions, and soaking time on the huff and puff effect, the best injection parameters were optimized. , CO 2 has a good extraction effect on shale oil. Some scholars studied the effects of injection pressure, soaking time, and fracture number on supercritical CO 2 extraction for shale oil from shale samples in Shengli Oilfield and found that light components could be extracted easily. CO 2 also has a strong diffusion effect. Some scholars had proved through experiments that CO 2 could diffuse into the matrix under the action of the pressure difference.…”
Section: Introductionmentioning
confidence: 99%
“…For the experimental study of indoor CO 2 huff and puff, some scholars compared the mining effects under N 2 and CO 2 injection by carrying out shale oil huff and puff experiments with N 2 and CO 2 injection, and verified the huge potential of CO 2 huff and puff in improving shale oil recovery. Also, by studying the effects of permeability, fracture, injection pressure, miscible conditions, and soaking time on the huff and puff effect, the best injection parameters were optimized. , CO 2 has a good extraction effect on shale oil. Some scholars studied the effects of injection pressure, soaking time, and fracture number on supercritical CO 2 extraction for shale oil from shale samples in Shengli Oilfield and found that light components could be extracted easily. CO 2 also has a strong diffusion effect. Some scholars had proved through experiments that CO 2 could diffuse into the matrix under the action of the pressure difference.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al studied the effect of the CO 2 concentration on crude oil PVT properties through huff and puff experiments. The results showed that with the increase in CO 2 concentration, the viscosity and density of the produced oil decreased, the light components in the crude oil increased, the heavy components decreased, and the content of paraffin and resin asphaltene decreased . Liu et al proposed that CO 2 molecular diffusion plays a major role in extracting the crude oil in macropores by the online nuclear magnetic resonance method and has little effect on the crude oil in micropores …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that with the increase in CO 2 concentration, the viscosity and density of the produced oil decreased, the light components in the crude oil increased, the heavy components decreased, and the content of paraffin and resin asphaltene decreased. 26 Liu et al proposed that CO 2 molecular diffusion plays a major role in extracting the crude oil in macropores by the online nuclear magnetic resonance method and has little effect on the crude oil in micropores. 27 During CO 2 huff and puff, injection parameters such as injection pressure, soaking time, injection timing, and huff and puff cycles are important factors affecting shale oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has been conducted on CO 2 huff-n-puff in tight sandstone reservoirs. Previous studies have explored the effects of injection volume, injection pressure, and huff-n-puff cycles on recovery efficiency. Ding et al considered the influence of four factors on CO 2 huff and puff times, matrix permeability, matrix size, and gas type and concluded that matrix permeability has a stronger influence on CO 2 huff and puff recovery than matrix size. Huang et al established a microreservoir classification standard based on field emission scanning electron microscopy (FE-SEM), CST, nanocomputed tomography (Nano-CT), HPMI, NMR, and other experimental methods, evaluating the influence of asphaltene content on pore structure and recovery efficiency.…”
Section: Introductionmentioning
confidence: 99%